2019
DOI: 10.21608/aasj.2019.67901
|View full text |Cite
|
Sign up to set email alerts
|

Effect of some light sources on broiler chickens performance under Assiut conditions, Egypt

Abstract: This study aimed to compare the effect of three different light sources on the growth performance and carcass quality of broiler chickens. Birds were wing banded, individually weighed and randomly assigned to three experimental groups, each including three equal replicates each of 15 chicks. Birds in groups 1, 2 and 3 were exposed to light emitted from incandescent (INC), saving (SAV) and Light Emitting Diodes (LED) lamps, respectively. The studied traits included (BW), (BWG), mortality rate, (FC), (FCR), carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
3
1
Order By: Relevance
“…This conforms to the remark of [15,42] that coloured polymer light filter had no significant (p>0.05) effect on liver, heart and gizzard weights. However, the result of the gizzard weight was not in line with the findings of [43] who indicated that there was significant (P<0.05) effect of gizzard weight under the different polymer light filter.…”
Section: Carcass and Organs Parameters Of Different Feed Form And Pol...contrasting
confidence: 76%
“…This conforms to the remark of [15,42] that coloured polymer light filter had no significant (p>0.05) effect on liver, heart and gizzard weights. However, the result of the gizzard weight was not in line with the findings of [43] who indicated that there was significant (P<0.05) effect of gizzard weight under the different polymer light filter.…”
Section: Carcass and Organs Parameters Of Different Feed Form And Pol...contrasting
confidence: 76%
“…Similarly, Kamanli et al (2015) revealed that LED lights reduced the mortality rate of birds. Ahmed et al (2019) also found that birds exposed to LED lighting had a lower mortality rate than those exposed to other lighting sources. Since yellow lighting has a shorter wavelength than orange lighting, birds exposed to yellow lighting tend to behave less aggressively and engage in cannibalism than those exposed to orange lighting.…”
Section: Mortality Ratementioning
confidence: 82%
“…Yang et al (2016) reported that LED lighting had superiority over the other sources of light regarding birds' FCR. Therefore, the use of LED lamps in poultry houses is highly recommended to maximize profits, especially with the gradual increase in the prices of feed ingredients worldwide (Ahmed et al 2019). On the other hand, Long et al (2016) reported that LED lamps are an excellent way to reduce electric costs.…”
Section: Feed Conversion Ratiomentioning
confidence: 99%
“…Furthermore, the findings revealed that reddish-hued LED lighting could increase the percentage of hens in lay at the beginning of the season (Archer, 2018). Moreover, Ahmed et al (2019) indicated using LED lighting in broiler production to maximize profit and reduce costs. Light sources significantly impact productive and reproductive qualities, welfare aspects, hormonal profile, and overall economics of layer production, according to Raziq et al 2021, with LEDs outperforming fluorescent and incandescent light sources.…”
Section: Light Sourcesmentioning
confidence: 98%